A review on the functional roles of trehalose during cryopreservation of small ruminant semen - Jia, Baoyu; Allai, Larbi; Li, Chunyan; Liang, Jiachong; Lv, Chunrong; Wu, Guoquan; Quan, Guobo (Frontiers in Veterinary Science, 2024)
Sperm cryopreservation is an approach to preserve sperm cells in liquid nitrogen or other cryogenic media for future use in assisted reproductive technologies, such as in vitro fertilization or artificial insemination. Sperm cryopreservation has been extensively used in the dairy industry and has attained excellent results after artificial insemination. However, for small ruminants the application of sperm cryopreservation is limited, due to the poor quality of frozen semen and special characteristics of the reproductive female tract. In order to improve post-thaw semen quality various cryoprotectants are used. Currently, many types of cryoprotectants, such as permeable organic solvents, sugars, antioxidants, and natural or synthetic ice blockers, have been tested on small ruminants’ sperm cryopreservation. Among them, trehalose; has shown potential acting as an excellent cryoprotectant for semen freezing. While, the exact roles and action mechanisms of trehalose during cryopreservation remain unclear. In this review, we systematically summarized the present usage status, potential action mechanisms, and future application prospects of trehalose in small-ruminant sperm cryopreservation.